Association between dietary antioxidant quality score and severity of coronavirus infection: a case–control study - Aghajani, Mobina; Wong, Alexei; Azimi, Mehdi; Harijani, Shadmehr Mirdar (Frontiers in Nutrition, 2023)
Aim: The purpose of this study was to examine the association between the dietary antioxidant quality score (DAQS) and coronavirus disease 2019 (COVID-19) severity. Method: The present case-control study was carried out on 295 patients diagnosed with COVID-19 (≥ 18 years old), including 104 critical patients (Intensive care unit [ICU] admission) and 191 COVID-19 patients without severe complications (Non-ICU patients) as cases. Dietary intake was assessed by the 147-item, semi-quantitative food frequency questionnaire (FFQ). Logistic regression was performed to calculate the odds ratio (OR) and 95% confidence interval (CI) for the considered risk factors. Results: Our outcomes (after multivariate adjustment) suggested that higher adherence to DAQS was significantly associated with decreased the risk of severity of COVID-19 infection (OR= 0.12; 95% CI: 0.04–0.29, p<0.001). Similar results were seen when analyzed by sex [men (OR =0.02; 95% CI: 0.002–0.15, p<0.001) and women (OR= 0.21; 95% CI: 0.06–0.68, p=0.012)]. A significant association between vitamin D3 intake and decreased risk of COVID-19 severity (OR= 0.91; 95% CI: 0.89–0.94, p<0.001) was also observed. Moreover, multivariate results revealed that there were no significant associations between vitamin C (OR= 1.00; 95% CI: 0.99–1.00, p=0.067), vitamin E (OR= 0.98; 95% CI: 0.86–1.11, p=0.798), zinc (OR= 1.02; 95% CI: 0.86–1.20, p=805), and selenium (OR= 0.99; 95% CI: 0.99–1.00, p=0.077) intakes with the risk of COVID-19 severity. However, subgroup analyses by sex suggested a significant association between vitamin C intake and risk of severity of COVID-19 infection in women (OR= 1.00; 95% CI: 1.00–1.00, p=0.028). Conclusion: Our findings showed a negative association between DAQS adherence and risk of COVID-19 infection severity. Our results may be used to develop potential dietary therapies to decrease COVID-19 severity.